Keystone management species under the Endangered Species Act can promote ecosystem-based management - Hayes, Sean A.; Roman, Joe (Frontiers in Conservation Science, 2026)
Human activities such as land conversion and resource consumption can cause species declines, which in the United States can result in listing for protection and recovery under the Endangered Species Act. Often highly charismatic species, such as bald eagles, grizzly bears, Pacific salmon, and North Atlantic right whales, get linked to human activity and social conflict emerges. This conflict can drive significant investment in a species’ recovery, including the suspension or alteration of multiple human activities, particularly when the species’ needs overlap with human activities such as food production, water management, and energy extraction. Analogous to keystone species, which directly influence their ecosystem through biological activity, we define these endangered and threatened species as keystone management species (KMS), because they prompt people to alter or undo their impacts on ecosystems through management activities that might not occur without that species’ charisma or social value. The phenomenon of these KMS under the ESA appears to be single species management at a surface level, but it is much more complex, often with cascading benefits to other species, while also increasing coordination across multiple sectors, resulting in ecosystem-based management. We review several case studies including the bald eagle’s emergence as one of the first KMS, following its dramatic recovery after the banning of DDT and widespread reintroduction projects; Pacific salmon’s influence on western land and water management and hydropower; the grizzly bear’s influence on western land and community waste management; and the North Atlantic right whale’s current influence on commercial fisheries and shipping and emerging influence on offshore aquaculture, marine renewable energy, and other marine activities.